A STUDY ON THE KNOWLEDGE AND ATTITUDES OF INDONESIAN WOMEN REGARDING MENSTRUAL CUPS AS ENVIRONMENTALLY FRIENDLY MENSTRUAL PRODUCTS - Alfiani, Fitri; Yuniko Febby H Fauzia; Azkya, Fharelina N (Universitas Muhammadiyah Ahmad Dahlan Cirebon, 2025)
Inadequate menstrual hygiene can increase the risk of reproductive tract infections, including pelvic inflammatory disease, dysmenorrhea, and infertility. Therefore, the use of safe and effective menstrual products is essential. Currently, disposable pads are widely recognized products. Disposable pad waste is deemed environmentally detrimental, leading to an estimated annual production of 113,000 tons. Menstrual cups are a viable long-term alternative, since they can be reused for up to ten years, effectively prevent leaks, accommodate various activities, and diminish the risk of toxic shock syndrome. Examining Indonesian women's knowledge and attitudes about menstrual cups is crucial, as it substantially aids in advancing the attainment of Sustainable Development Goals (SDGs). Procedure. This was a quantitative study utilizing anonymous web-based questionnaires. Outcomes. Of the Indonesian women, 75.97% possessed limited knowledge, while only 24.03%weree well-informed about menstruation cups as eco-friendly menstrual devices. 85.06% of Indonesian women were disinclined to utilize menstruation cups, while only 14.94% expressed a willingness to adopt these environmentally friendly menstrual devices. The ?-value was 0.514>0.05, which represents statistical insignificance; hence, knowledge was not associated with attitude. Keywords: attitude; knowledge; menstrual_cup; menstruation; women_health